Efficacy and tolerability of liposomal polyvinylpyrrolidone-iodine hydrogel for the localized treatment of chronic infective, inflammatory, dermatoses: an uncontrolled pilot study - Augustin M; Goepel L; Jacobi A; Bosse B; Mueller S; Hopp M (Dove Medical Press, 2017)
Matthias Augustin,1 Lisa Goepel,2 Arnd Jacobi,2 Bjoern Bosse,3 Stefan Mueller,3 Michael Hopp3 1Department of Dermatology, University-Hospital Freiburg, Freiburg, 2Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf, University of Hamburg, Hamburg, 3Mundipharma Research GmbH & Co.KG, Limburg (Lahn), Germany Abstract: Infection is common in many chronic, inflammatory skin conditions but is often difficult to treat, in part due to growing bacterial resistance to antibiotics. Liposomal polyvinylpyrrolidone (PVP)-iodine hydrogel has a unique mode of action, combining the antiseptic and anti-inflammatory actions of PVP-iodine with the drug delivery and moisturizing properties of liposomes. We investigated the utility of liposomal PVP-iodine to treat infective dermatoses. In this prospective, single-arm (uncontrolled), open-label Phase II pilot study, patients with acne vulgaris (n=30), atopic dermatitis (n=20), impetigo contagiosa (n=10), and rosacea (n=10) received PVP-iodine (3%) hydrogel for ≤4 weeks. Global Clinical Severity score improved for all dermatoses (range: 0.5 for acne vulgaris [p<0.001] to 1.0 for impetigo contagiosa [p=0.011]). Improvements in pain, quality of life, (Freiburg Life Quality Assessment), and Eczema Area and Severity Index scores were also seen. Treatment was well tolerated; most frequent adverse events were burning (14%) or itching (9%) sensations. Thus, liposomal PVP-iodine hydrogel has potential utility as an effective treatment for inflammatory skin conditions associated with bacterial colonization. Keywords: acne vulgaris, atopic dermatitis, impetigo contagiosa, liposomal PVP-iodine hydrogel, polyvinylpyrrolidone, rosacea